Assessment of the ability of mangroves to serve as accumulated Carbon sinks in the plantations in Kim Dong Commune, Kim Son District, Ninh Binh Province, Vietnam - Hong Hanh, Nguyen Thi (Academia Journal of Biology, 2017)
Kim Dong is one of the three coastal communes in Kim Son District, Ninh Binh Province in the Red River Delta; Kim Dong is covered with 573.5 ha of mangrove plantations with dominant species of Kandelia obovata and Sonneratia caseolaris. The aim of this study is to assess the ability of mangroves to form carbon sinks in soil to support the state management of greenhouse gas emission reduction. The results are assumed to be used as a scientific basis and information for international negotiations on programs to cut greenhouse gas emissions, such as REDD and REDD+. For this purpose, we quantified the amount of carbon stored in the soil of Kandelia obovata mangroves aged 5, 4 and 3 years old in Kim Dong Commune, Kim Son District, Ninh Binh Province, Vietnam. The results showed that in K. obovata mangrove soil, carbon accumulation was age-dependent and the highest value was in the 5 year old one at 73.211 tons/ha. The annual cumulative carbon added to the mangrove soil (estimated by equivalent CO2) is also age-dependent and the 5-year-old mangroves accumulated the highest amount, 12.525 tons/ha/year (equivalent to 45.967 tons of CO2/ha/year). From our results, the ability of mangroves to accumulate carbon in the soil is high, and this fact serves a scientific basis to develop and implement projects of mangroves planting, combined with conservation, sustainable management and enhancement of carbon stocks of mangrove plantations in the coastal strips of Vietnam.